Prescribing of non-steroidal anti-inflammatory drugs, tramadol and opioids in children: patterns of its utilization - Zin, Che Suraya (2019)
Background: Analgesic is commonly used in children but little is known about its patterns of utilization. This study explored the patterns of analgesic prescribing in children.